Potential biomarker enhancing the activity of tuberculosis, hsa-miR-346. (July 2021) - Uno, Shunsuke; Nishimura, Tomoyasu; Nishio, Kazumi; Kohsaka, Asami; Tamizu, Eiko; Nakano, Yasushi; Kagyo, Junko; Nakajima, Yukiko; Arai, Ryosuke; Hasegawa, Hanako; Arakawa, Kenichi; Kashimura, Shoko; et al.
Abstract: Objectives: To determine the usefulness of hsa -miR-346, a potential biomarker enhancing the activity of non-tuberculous mycobacterial diseases, as a biomarker of tuberculosis activity. Methods: We investigated whether hsa -miR-346 is secreted by human macrophages infected with Mycobacterium tuberculosis ( M. tuberculosis ) in an in vitro study. In addition, a cross-sectional study was conducted first to evaluate whether serum hsa -miR-346 is elevated in patients with tuberculosis compared with that in healthy individuals. Second, we conducted a retrospective study to evaluate whether anti-tuberculosis treatment reduces serum hsa -miR-346 levels. Results: Log hsa -miR-346 levels were significantly elevated in the supernatant of human macrophages infected with M. tuberculosis in a dose-dependent manner. The mean serum log hsa -miR-346 levels were −15.48 (−15.76 to −15.21) in patients with tuberculosis and −16.12 (−16.29 to −15.95) in healthy volunteers, which significantly differed. In addition, hsa -miR-346 significantly decreased at 2 months from starting an anti-tuberculosis treatment. Conclusions: We consider hsa -miR-346 as a potential biomarker enhancing the tuberculosis activity. Highlights: Treatment monitoring is essential for the appropriateness of tuberculosis treatment. Biomarkers that predict tuberculosis treatment outcomes are needed. We found hsa -miR-346 was secreted from by human macrophages infected with M. tuberculosis . Serum hsa -miR-346 level declined during the second month of treatment with bacteriological improvement. We added hsa -miR-346 as a potential biomarker enhancing the tuberculosis activity.